A phylogenetic approach to study the origin and evolution of the CRINKLY4 family - Nikonorova, Natalia; Vu, Lam D.; Czyzewicz, Nathan; Gevaert, Kris; De Smet, Ive (Frontiers in Plant Science, 2015)
Cell–cell communication plays a crucial role in plant growth and development and relies to a large extent on peptide ligand–receptor kinase signaling mechanisms. The CRINKLY4 (CR4) family of receptor-like kinases is involved in a wide range of developmental processes in plants, including mediating columella stem cell identity and differentiation in the Arabidopsis thaliana root tip. Members of the CR4 family contain a signal peptide, an extracellular part, a single-pass transmembrane helix and an intracellular cytoplasmic protein kinase domain. The main distinguishing features of the family are the presence of seven “crinkly” repeats and a TUMOR NECROSIS FACTOR RECEPTOR (TNFR)-like domain in the extracellular part. Here, we investigated the evolutionary origin of the CR4 family and explored to what extent members of this family are conserved throughout the green lineage. We identified members of the CR4 family in various dicots and monocots, and also in the lycophyte Selaginella moellendorffii and the bryophyte Physcomitrella patens. In addition, we attempted to gain insight in the evolutionary origin of different CR4-specific domains, and we could detect “crinkly” repeat containing proteins already in single celled algae. Finally, we related the presence of likely functional CR4 orthologs to its best described signaling module comprising CLAVATA3/EMBRYO SURROUNDING REGION-RELATED 40 (CLE40), WUSCHEL RELATED HOMEOBOX 5 (WOX5), CLAVATA 1 (CLV1), and ARABIDOPSIS CR4 (ACR4), and established that this module likely is already present in bryophytes and lycophytes.